Penguatan Kompotensi Guru Dalam Pengembangan Perangkat Pembelajaran Tematik - Integrated Berbasis Pendekatan Saintifik di SD Gugus Umamapu Waingapu Kabupaten Sumba Timur - hiwa wonda; Sofia G. Un Lala; Bella Theo Tomi Pamungkas; Fernando Saragih (Universitas Nusa Cendana, 2023)
Elementary school education today, in the first decade of the 21st century, is faced with global challenges where people's life patterns change very quickly, triggered mainly by developments in information technology and global challenges. This community service is offered to solve the problems faced by the teacher group at SD Gugus Umamapu Waingapu Elementary School, East Sumba Regency. Looking at the partner's problems, the implementation method offered in service to solve the problems faced by the group of SD Gugus Umamapu Waingapu Elementary School teachers, East Sumba Regency are (1) Knowledge of designing lesson plans, (2) The teacher's knowledge of learning tools is not maximized, (3) The teacher's ability in developing learning tools still varies. To achieve the goal, community service activities are carried out in the form of training. Training activities are designed with the stages of the service cycle such as the stages of the Classroom Action Research (PTK) cycle. The stages of the PTK cycle consist of planning, action, observation and reflection activities. The PTK stages are used as a reference for the stages of training activities at this trial. The proposed method to solve the problem that has been formulated is divided into three stages, namely the preparation, implementation, observation and reflection stages. Strengthening Teacher Competence in Developing Thematic Learning Devices - Integrated Based on a Scientific Approach at Gugus Umamapu Waingapu Elementary School, East Sumba Regency, received a very positive response as shown from the reflection results at the end of the mentoring. Service activities are categorized as achieving activity objectives because there is an increase 1) 40% of teachers are able to design lesson plans with mapping indicators in the good category, 2) 40% of teachers are able to design lesson plans with appropriate learning strategies to achieve learning objectives, 3) 40% of teachers are able to design stages learning with inquiry learning strategies to achieve learning indicators, 4) 10% of teachers are able to choose appropriate learning media to teach students with appropriate learning strategies.